Do the Learners are inclining towards the student credit card scheme? the reality and its prospect - Bar, Koushik; Patra, Anujit; Guha, Abhijit (International Journal of Educational Innovation and Research, 2024)
Recently, taking an educational loan is a major concern of matter in the economics of education research. The researchers attempted to understand the perception of postgraduates’ students about the student credit card scheme launched by the state government of West Bengal in India. Three hundred fifty-four students were chosen randomly from 12 universities. Five points Likert-type scale was used to measure the perception of the students about student credit card. The researchers used a quasi-mixed method. Data were analysed by the use of descriptive, inferential statistics and also qualitatively by thematic analysis. The study found that the perception of the postgraduates ‘students about student credit card schemes has changed significantly due to their duration of study in university. But, perception about the same scheme has not been influenced by gender, age, academic stream, residential location, family income, caste category, availed or not of the scheme. Study also found that thirty six percent of students are satisfied with the scheme. On the other side large percent (47%) students are opposing the scheme in terms of either they feel not satisfied directly, or criticise this policy due to various reasons. However, some students favour it as the scheme has an inherent motive to promote students to receive higher education.